Atypical Gastric Ulcer in an Elderly Cocaine User. (30th July 2013) - Gaduputi, Vinaya; Tariq, Hassan; Ihimoyan, Ariyo
Abstract : Cocaine or Benzoylmethylecgonine is an alkaloid extracted from the leaves of the Erythroxylon plant, which can cause gastrointestinal ischemia from severe arterial vasoconstriction via stimulation of alpha-adrenergic receptors in the gastric and mesenteric arteries. We report this case of a 65-year-old man who presented with a single massive ulcer at the incisura of the stomach as a result of cocaine use. The size and location of this ulcer were atypical and illustrate the potential for serious gastrointestinal manifestations from cocaine use.